Analysis Of Speech Acts Of Dayak Ngaju Language In Parahangan Village, Pulang Pisau District, Central Kalimantan - Handoko; Ni Made Anggi Arlina Putri; Sulandra; Hendri (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2024)
The speech act is a linguistic phenomenon that occurs in society, one of which is the Ngaju Dayak community. The Dayak Ngaju people are one of the Dayak tribes in Central Kalimantan. This study aimed to describe: 1) directive speech acts’ types in Dayak Ngaju language in Pulang Pisau district, 2) the functions of directive speech acts in Dayak Ngaju language in Pulang Pisau district, 3) factors which is caused directive speech acts in Dayak Ngaju language in Pulang Pisau Regency. Descriptive qualitative research was adopted to use in this study. In selecting the sample, the researchers used purposive sampling so that the data obtained is more representative. The researcher used observation, interviews, and taking notes to collect the data. The results state that: 1) Directive speech acts types of the Dayak Ngaju language in Parahangan village, Pulang Pisau Regency, belong to direct and indirect directive speech acts, 2) directive speech acts’ functions in the Dayak Ngaju language in Parahangan village, Pulang Pisau Regency, consist of six functions, namely directive speech acts of commands, orders, requests, prohibitions, invitations and giving suggestions, 3) several aspects influence a speech act namely: (1) the speaker/partner, (2) the purpose of the speech, (3) and social distance.